Criteria used for the active surveillance of localised prostate cancer in the UK. (January 2015) - Hawizy, A; Salji, M; Kelker, AR; Gujral, SS; Van As, N
Introduction: Active surveillance (AS) is a valid option for localised prostate cancer and should be offered to patients who are suitable for radical treatment in conjunction with current NICE guidelines. The aim of this study was to evaluate the consensus on AS selection and follow-up criteria in the United Kingdom (UK). Method: An electronic survey (Appendix 1) was emailed to 500 British Association of Urological Surgeons (BAUS) members to determine their local criteria for active surveillance in prostate cancer. Results: Of the 134 (26.8%) BAUS members who responded, PSA ≤ 10 ng/ml, Gleason score ≤ 6 and clinical stage ≤ T1c were the preferred selection criteria used in the UK. However, only 51.5% will perform MRI for disease staging. Most urologists (65.6%) preferred three-monthly PSA follow-up visits for the first year then six-monthly thereafter. A digital rectal examination (DRE) is not performed by 57.1%. Increased Gleason score and PSA doubling time were the two main criteria that would trigger intervention. Conclusion: There is a lack of consensus on criteria used for selection, follow-up and repeat biopsy for prostate cancer patients on active surveillance in the UK.